The Effect of Water-level on the Rainfall of a Locality - Sahay, B. K. (Indian Forester, 1952)
Indications are forthcoming that it is possible to predict the rainfall of a locality from a study of the comparative minimum water-levels of a lake or reservoir in the summer before the break of the monsoons.